2015
DOI: 10.1542/peds.2014-3550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Intracranial Abnormalities in Unprovoked Seizures

Abstract: BACKGROUND AND OBJECTIVES: Prospective data are lacking to determine which children might benefit from prompt neuroimaging after unprovoked seizures. We aimed to determine the prevalence of, and risk factors for, relevant intracranial abnormalities in children with first, unprovoked seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
4
16
2
Order By: Relevance
“…This study however only included 11% of patients with seizure > 15 minutes, and seizure duration > 15 minutes was associated with an increased incidence of abnormal neuroimaging findings. 24 Our data add and expand to the previously reported yield of neuroimaging; in this cohort of children with new-onset seizure and status epilepticus we found of 36% of children with abnormal neuroimaging of which 8.5% had pathology requiring urgent or emergent interventions.…”
Section: Discussionsupporting
confidence: 81%
“…This study however only included 11% of patients with seizure > 15 minutes, and seizure duration > 15 minutes was associated with an increased incidence of abnormal neuroimaging findings. 24 Our data add and expand to the previously reported yield of neuroimaging; in this cohort of children with new-onset seizure and status epilepticus we found of 36% of children with abnormal neuroimaging of which 8.5% had pathology requiring urgent or emergent interventions.…”
Section: Discussionsupporting
confidence: 81%
“…We enrolled 475 of 625 (76.0%) eligible children (comparisons between those who were and not enrolled are detailed in parent manuscript) . Of the 475 patients, we excluded 27 patients from all analyses for the following reasons: a clear precipitant was present ( n = 12), the event was not a seizure based on follow‐up telephone call ( n = 9), or the seizure was either an absence seizure or a prevalent (not incident) seizure ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…We performed a secondary analysis of data from a prospective cohort study of children who presented with seemingly unprovoked seizures to any of six urban, university‐affiliated pediatric EDs in the US between March 2005 and September 2007. The parent study assessed the risk of intracranial abnormalities in children with first unprovoked seizures . Each center's institutional review board approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of interrater agreement have focused on physician-physician or physician-nurse dyads. [26][27][28] We demonstrated that the overall percentage agreement was high for all modified Centor score predictors between the clinician and patient or parent. When we evaluated the κ, however, which measures agreement beyond chance alone, the agreement for historical symptoms was moderate or high and lower for clinical examination findings.…”
Section: Figurementioning
confidence: 99%